Narratives of Emancipation in Modern Islam: Temporality, Hermeneutics, and Sovereignty - Tareen, SherAli (Islamic Studies, 2013)
This essay examines certain key epistemological assumptions and positions found in the thought of prominent modern Muslim scholars, as they imagined the interaction of Islam and the conditions of colonial modernity. The event of colonialism in the nineteenth century, and its twin ideology of modernity, transformed the political and conceptual terrain on which the question of Islam was imagined and contested. While operating in this new terrain, Muslim scholars reconfigured the conceptual underpinning of Islam in novel ways, as they strived to curate an intellectual programme for the moral and political emancipation of Muslims. In what follows I highlight major features of some of these intellectual programmes. Specifically, I address the question of how Muslim scholars conceptualised the ideas of temporality, hermeneutics, and sovereignty during the colonial moment. The central focus of this essay is on the religious and political thought of the towering twentieth-century Indian Muslim modernist Muhammad Iqbal (d. 1939) as seen in his important English text The Reconstruction of Religious Thought in Islam published in 1930. I also juxtapose Iqbal’s thought with that of the famous Islamist thinker/activist Sayyid Qutb (d. 1966) to think through some of the epistemological convergences between Muslim modernist and Islamist/fundamentalist thought on questions of time and sovereignty.